1966
DOI: 10.1002/1097-0142(196605)19:5<611::aid-cncr2820190503>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of forty-nine patients with malignant melanoma

Abstract: A study of 49 patients with malignant melanoma of the skin occurring over an 18‐year period is presented. The over‐all 5‐year survival was 43%. The prognosis was uniformly better for females and for lesions less than one cm. A poor prognosis was associated with primary lesions on the trunk, ulceration or hemorrhage of the primary and clinically and microscopically positive nodes. The authors conclude that a wide local excision of the primary lesion, including a 3 to 5 cm margin of skin, combined with an in‐con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1967
1967
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…For the closure of large skin defects, we frequently applied the bilobed rotation pedicle flap, mostly on the trunk 13 . Contrary to other examiners’reports, 14,15 we did not observe any local recurrences within 3.5 years because of the primary closure. This method proved to be especially superior to skin graft, if the melanoma was located on the back.…”
Section: Commentscontrasting
confidence: 99%
See 1 more Smart Citation
“…For the closure of large skin defects, we frequently applied the bilobed rotation pedicle flap, mostly on the trunk 13 . Contrary to other examiners’reports, 14,15 we did not observe any local recurrences within 3.5 years because of the primary closure. This method proved to be especially superior to skin graft, if the melanoma was located on the back.…”
Section: Commentscontrasting
confidence: 99%
“…In addition, it reduces the size of the wound. With the final transposition of the relatively small lobes, large defects of up to a diameter of 15 cm can be closed without the use of additional skin grafts.…”
Section: Local Proceduresmentioning
confidence: 99%
“…24 The influence of the sex of the patient has been previously reported, women having a better prognosis than men. [25][26][27][28][29][30][31][32][33][34][35] Although multivariate analysis, in some studies, failed to demonstrate prognostic significance for sex,*' or its effect was thought to be mediated through anatomic location: the bulk of the literature has consistently pointed out the prognostic significance of sex regarding survival. Our current study supports this view and suggests that survival of men and women should be considered separately.…”
Section: Discussionmentioning
confidence: 99%
“…Although Elias and others 5 reported the same survival rates for patients treated with excisions large enough to require skin grafting as for those treated with excisions small enough to permit primary closure, they found more local recurrences in the primary‐closure group. Lehman and coworkers, 6 in contrast, showed that excisions large enough to require skin grafts reduced both the melanoma mortality rate and the number of local recurrences. These studies comparing skin grafting versus primary closure are difficult to interpret because the width of the margins of excision was not reported.…”
Section: Skin Grafting Versus Primary Closurementioning
confidence: 99%